PENGARUH PANDEMI COVID-19 TERHADAP KINERJA UMKM DI KOTA JAMBI PADA TAHUN 2020 - Muhammad Rafi Bakri (Politeknik Keuangan Negara STAN, 2021)
The Covid-19 pandemic has had an enormous impact, especially for SMEs in Jambi City. This study aims to empirically assess the effect of the pandemic on the performance of MSMEs in Jambi City. The research method used is a quantitative analysis using a simple linear regression method. Data was obtained by distributing questionnaires to MSME actors in Jambi City. he results showed that the pandemic had a relationship of 0.317 or 31.7% on the performance of MSMEs in Jambi Province. Through simple linear regression, the effect of the pandemic on the performance of MSMEs in Jambi City is -46.2%. This harmful and significant influence causes the performance of MSMEs to decline during the pandemic.